Revision of the Malagasy genus Lechius Iwan, 1995 (Coleoptera: Tenebrionidae: Pedinini) - Iwan, Dariusz; Kamiński, Marcin Jan (Zootaxa, 2012)
The taxonomic concept of the genus Lechius Iwan, 1995 and the hypotheses of all its species, are tested basing on newlyavailable material from Madagascar. Comparative analysis showed that the male and female genitalia most apparently re-flect the evolutionary trends within this genus. Two new Lechius species are described: L. aalbui sp. nov. and Lechiuslongiclavis sp. nov. A distributional map is presented with complete faunistic data on the genus. An identification key is provided to all known species of Lechius.